New data on the location of the snow leopard Panthera uncia (Schreber, 1775) and the stone marten Martes foina (Erxleben, 1777) in the Katon-Karagai State National Natural Park (Kazakhstan Altai) - Gabdullina, Aliya U.; Amanbaev, Zhomart B.; Kasymov, Erik T. (Acta Biologica Sibirica, 2021)
The article provides new data on the location and distribution of the snow leopard Panthera uncia and the stone marten Martes foina in the Katon-Karagai State National Natural Park (South-Western Altai, Eastern Kazakhstan). The data were obtained using camera traps.